Mathematics in the modern world - Baltazar, Ethel Cecille; Ragasa, Carmelita ; Evangelista, Justina (Quezon City C & E Publishing, 2018)
The book covers the mandated topics and some of the elective ones which are all organized in a logical fashion.
Keywords: Mathematics